Hollow-fiber bioreactor production of extracellular vesicles from human bone marrow mesenchymal stromal cells yields nanovesicles that mirrors the immuno-modulatory antigenic signature of the producer cell - Gobin, Jonathan; Muradia, Gauri; Mehic, Jelica; Westwood, Carole; Couvrette, Lauren; Stalker, Andrew; Bigelow, Stewart; Luebbert, Christian C; Bissonnette, Frédéric S; Johnston, Michael J W; Sauvé, Simon; Tam, Roger Y; et al. (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Extracellular vesicles (EVs) produced by human bone marrow-derived mesenchymal stromal cells (hBM-MSCs) are currently investigated for their clinical effectiveness towards immune-mediated diseases. The large amounts of stem cell-derived EVs required for clinical testing suggest that bioreactor production systems may be a more amenable alternative than conventional EV production methods for manufacturing products for therapeutic use in humans. Methods To characterize the potential utility of these systems, EVs from four hBM-MSC donors were produced independently using a hollow-fiber bioreactor system under a cGMP-compliant procedure. EVs were harvested and characterized for size, concentration, immunophenotype, and glycan profile at three separate intervals throughout a 25-day period. Results Bioreactor-inoculated hBM-MSCs maintained high viability and retained their trilineage mesoderm differentiation capability while still expressing MSC-associated markers upon retrieval. EVs collected from the four hBM-MSC donors showed consistency in size and concentration in addition to presenting a consistent surface glycan profile. EV surface immunophenotypic analyses revealed a consistent low immunogenicity profile in addition to the presence of immuno-regulatory CD40 antigen. EV cargo analysis for biomarkers of immune regulation showed a high abundance of immuno-regulatory and angiogenic factors VEGF-A and IL-8. Conclusions Significantly, EVs from hBM-MSCs with immuno-regulatory constituents were generated in a large-scale system over a long production period and could be frequently harvested with the same quality and quantity, which will circumvent the challenge for clinical application.